Insecticidal Activity of Some Plant Extract Against Greater Wax Moth Larvae (Galleria mellonella L.) - Shalaw Abdalrahman Omer; Ibrahim Majeed Faraj; Nask Muhamad Faraj (Agricultural Science, 2023)
Galleria mellonella L. (Lepidoptera: Pyralidae) is a significant international pest and the most devastating pest throughout the world of beeswax. Natural pesticides must be replaced with synthetic materials since they are more ecologically friendly. This study aims to determine alternative methods of controlling the larger wax moth by assessing the efficacy of several plant-based biocides for this purpose various ethanolic plant extracts such as rosemary (Rosmarinus officinalis L), Clove (Syzygium aromaticum), Eucalyptus (Eucalyptus sp) and Cinnamon (Cinnamomum verum) where used with four extraction rates (5,10,15 and 20) against the late instar larvae of Galleria mellonella in vitro after 24,48 and 72 hr. Obtained results revealed that the pupal mortality increased when the concentration increased and the highest accumulative mortality percentage of wax moth larvae during the experiment, it was demonstrated that all studied plants were efficient at suppressing Galleria mellonella larvae. The result shows that three days after application treatment of rosemary 20% gave the maximum total mortality percentage (%100) followed by (%96.58, %92.66 and %64.86) for Eucalyptus, Cinnamon and clove after 24,48 and 72 hr. respectively. It may be suggested that spraying natural products is a good option on new wax combs to protect them against infestation by wax moth larvae